Comportamientos auto-protectores para la prevención del abuso sexual infantil enfocado a los estudiantes del grado 401 de una institución educativa de Riohacha. (2023)
Child sexual abuse has become a public health problem that, in most cases, interferes with the proper development of the child who suffers it and negatively affects their physical, emotional and psychological state. For this reason, it is essential to recognize the capacities and needs of the stage in which each child and/or adolescent is so that the adults responsible for them can generate spaces of trust and security and create self-protection mechanisms together. The purpose of this research is to identify the learning of self-protective behaviors for the prevention of child sexual abuse in the students of 4°1 of the Happy Kids teaching and stimulation center. A quantitative, cross-sectional study was carried out with a design quasi-experimental pre-test post-test and with an exploratory scope.